Integrating self-determination theory and theory of planned behavior to strengthen entrepreneurial intention among undergraduate students - Al Jubari, Ibrahim Hizam Ali; Hassan, Arif (2012)
It is well established that entrepreneurship is a major contributor to the growth of wealth and well-being of societies. It is increasingly getting more recognized among researchers, practitioners and policy makers around the globe. It directly affects the development of nations’ economies by creating jobs and transforming people’s lives through innovation and technology. It is observed that when nations promote entrepreneurship, they become more competitive and have advantage over other nations. Promoting entrepreneurship encourage people, especially the youth, to produce new ideas and help them transform those ideas into tangible services or products. It is also noticed that it reduces the pressure on governments of the unemployment by not only securing jobs for entrepreneurs themselves, but also it is likely that those entrepreneurs will employ others as well.